Belize : Assessment Letter for the International Financial Community. (Policy Papers; Policy Paper ;, 2006)
Assessment letters or statements may be prepared for member countries with Fund-supported programs; receiving Fund emergency assistance; with staff-monitored programs; or surveillance-only cases. They are typically produced for use by the country with multilateral or bilateral donors or creditors, in particular the World Bank and other International Financial Institutions.